2020
DOI: 10.1007/s00125-020-05268-4
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbial metabolites in human metabolism and type 2 diabetes

Abstract: Humans with the metabolic syndrome and type 2 diabetes have an altered gut microbiome. Emerging evidence indicates that it is not only the microorganisms and their structural components, but also their metabolites that influences the host and contributes to the development of the metabolic syndrome and type 2 diabetes. Here, we discuss some of the mechanisms underlying how microbial metabolites are recognised by the host or are further processed endogenously in the context of type 2 diabetes. We discuss the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 140 publications
1
44
0
2
Order By: Relevance
“…The role of gut microbiota-derived metabolites in the development of cardiovascular disease has gained recent attention [ 11 ], particularly in individuals with T2D [ 34 ]. Nevertheless, the association of TMAO with risk of cardiovascular mortality in subjects with T2D has not being sufficiently studied.…”
Section: Discussionmentioning
confidence: 99%
“…The role of gut microbiota-derived metabolites in the development of cardiovascular disease has gained recent attention [ 11 ], particularly in individuals with T2D [ 34 ]. Nevertheless, the association of TMAO with risk of cardiovascular mortality in subjects with T2D has not being sufficiently studied.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the α-glucosidase inhibitory and α-amylase inhibitory activities of probiotics may be beneficial for glycemic regulation [ 28 , 29 ]. Probiotics have been reported to alleviate T2DM by regulating glucose metabolism and improving insulin sensitivity through several mechanisms, including the production of metabolites, such as SCFAs [ 30 , 31 ]. Some probiotic strains have been reported to produce bioactive components capable of inhibiting α-glucosidase activity [ 15 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, further studies are needed to address whether alterations in gut microbiome in humans is a cause of type 2 diabetes or is an outcome of it. [ 93 , 95 , 96 , 97 , 98 ]…”
Section: Glucagon Signalingmentioning
confidence: 99%